The Effect of Incorporation of Cellulose Kenaf Fibers in Composite Resin on Mechanical Properties and Surface Topography Analysis Using Scanning Electron Microscopy - Ibrahim, Nur Aliya; Alawi, Rabihah; Johari, Yanti; Muttlib, Nor Aidaniza Abdul; Yusoff, Mohd Nazrulhuzaimi Md (European Journal of General Dentistry, 2021)
Objective This study aimed to evaluate the flexural and compressive strength of kenaf-reinforced composite resin as well as analyze the length and diameter of kenaf fibers and their surface topography.Materials and Methods Kenaf fibers were alkaline treated and wetted with coupling agent. Kenaf-reinforced composite resin was fabricated manually. Specimens for kenaf-reinforced composite resin (Tetric N Flow [Ivoclar Vivadent, Liechtenstein] + 2% kenaf) and control group (Tetric N Flow [Ivoclar Vivadent, Liechtenstein]) were prepared using stainless steel molds with dimension of 25 mm × 2 mm × 2 mm and 6 mm × 4 mm for flexural and compressive strength tests, respectively, and tested using Instron Universal Testing Machine (Shimadzu, Japan). Raw kenaf fibers, treated kenaf fibers, and fractured sample from flexural strength test were analyzed using scanning electron microscopy (SEM) (FEI Quanta FEG 450, United States). Data were analyzed using independent sample t-test. Significant level was set at p < 0.05.Results Kenaf-reinforced composite resin has a lower flexural and compressive strength than the control group (p < 0.05). SEM analysis revealed the average fibers’ length to be 1.24 mm and diameter ranging from 6.56 to 12.9 μm. The fibers dispersed in composite as single strand or a bundle with a minimal gap between fibers and composite.Conclusion Flexural and compressive strengths of kenaf-reinforced composite resin were lower than the control group, despite some adaptation between kenaf fibers and composite noted. The fibers’ length and diameter were reasonable for the dispersion in the resin matrix; however, additional treatments of kenaf are required for a favorable result.
Keywords: kenaf fibers; fiber-reinforced composite; flexural strength; compressive strength